Algorithm of microchip operation for controlling parameters of a latex agglutination reaction - Bilyi, O.I.; Yaremyk, R.Y.; Kiselyov, Y.M.; Novikov, V.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
In the given work the algorithm of work and structure of microchip construction, intended for kinetics researches of formation of modular complexes is considered during the reaction of latex agglutination. The physical principles of registration of enzyme adsorption isotherms on latex by method of light scattering are considered. The results of the reaction of adsorption of protacrin enzyme on hydroperoxide latex’s are shown.